The Effect of Cesarean Delivery Skin Incision Approach in Morbidly Obese Women on the Rate of Classical Hysterotomy - Brian E. Brocato; Edwin M. Thorpe; Luis M. Gomez; Jim Y. Wan; Giancarlo Mari (Journal of Pregnancy)
Objective. To assess the risk of classical hysterotomy and surgical morbidity among women with a body mass index (BMI) greater than 40 kg/m2 who underwent a supraumbilical incision at the time of cesarean delivery. Methods. We conducted a retrospective cohort study in women having a BMI greater than 40 kg/m2 who underwent a cesarean delivery of a live, singleton pregnancy from 2007 to 2011 at a single tertiary care institution. Intraoperative and postoperative outcomes were compared between patients undergoing supraumbilical vertical (cohort, ) or Pfannenstiel (controls, ) skin incisions. Results. Women undergoing supraumbilical incisions had a higher risk of classical hysterotomy (OR, 24.6; 95% CI, 9.0–66.8), surgical drain placement (OR, 6.5; 95% CI, 2.6–16.2), estimated blood loss greater than 1 liter (OR, 3.4; 95% CI, 1.4–8.4), and longer operative time (97 ± 38 minutes versus 68 ± 30 minutes; ) when compared to subjects with Pfannenstiel incisions (controls). There was no difference in the risk of wound complication between women undergoing supraumbilical or Pfannenstiel incisions (OR, 2.7; 95% CI, 0.9–8.0). Conclusion. In women with a BMI above 40 kg/m2, supraumbilical incision at the time of cesarean delivery is associated with a greater risk of classical hysterotomy and operative morbidity.